Candiduria: Prevalence, Identification of Isolated Candida Species and Trends in Antifungal Susceptibility in Hospitalized Patients - Ghasemi, Reza; Rabiei, Mohammad Mahdi; Lotfali, Ensieh; Abolghasemi, Sara; Ansari, Saham (Novelty in Biomedicine, 2020)
Background: Urinary tract candidiasis is known as the most frequent nosocomial fungal infection worldwide. Some of the predisposing factors of candiduria are extensive use of broad-spectrum anti-fungal agents, diabetes mellitus, indwelling urinary catheter, corticosteroids and, immunosuppressive drugs. There are some antifungal agents available for the treatment of candiduria. In recent years, resistance to antifungal agents has been increased. The aim of this study was to evaluate different Candida species (sp.) that cause candiduria and their susceptibility pattern to antifungal agents in patients admitted to educational hospitals. Materials and Methods: Urine samples (n=200) were obtained; they were spread onto Sabouraud Dextrose Agar plates. Plates were incubated at 37°C. Only specimens were considered as candiduria, which have a colony count of ≥104 CFU/mL colonies. Urine sediment was cultured in the CHROM agar Candida medium and incubated at 35°C for 48h. The cultures were evaluated based on color. PCR-RFLP was performed for a definite identification of Candida sp. In vitro antifungal susceptibility test of the Candida isolates against amphotericin B, fluconazole and itraconazole was performed using the microdilution method, according to the standard CLSI guidelines, document M27-S3. Results: Molecular findings confirmed the result of the morphological method. Candiduria rate was 11.5% among our patients. According to CHROM agar Candida and PCR-RFLP, the most common species isolated was C. albicans (74%), followed by C. glabrata (26%). In vitro susceptibility tests of urinary Candida isolates to antifungals have been evaluated. All species were sensitive to amphotericin B. None of C. glabrata isolates were sensitive to fluconazole and itraconazole. Conclusion: This study demonstrates the importance of Candida sp. in urine samples from hospitalized patients. It was concluded that Candida sp. obtained from candiduria in patients had excellent activity against Amphotericin B. Whereas, resistance against Itraconazole (21.7%) and especially Fluconazole (26%) was significant.